Determining optimal timing of birth for women with chronic or gestational hypertension at term: The WILL (When to Induce Labour to Limit risk in pregnancy hypertension) randomised trial. - Laura A Magee; Katie Kirkham; Sue Tohill; Eleni Gkini; Catherine A Moakes; Jon Dorling; Marcus Green; Jennifer A Hutcheon; Mishal Javed; Jesse Kigozi; Ben W M Mol; Joel Singer; et al. (PLoS Medicine)
Background Chronic or gestational hypertension complicates approximately 7% of pregnancies, half of which reach 37 weeks' gestation. Early term birth (at 37 to 38 weeks) may reduce maternal complications, cesareans, stillbirths, and costs but may increase neonatal morbidity. In the WILL Trial (When to Induce Labour to Limit risk in pregnancy hypertension), we aimed to establish optimal timing of birth for women with chronic or gestational hypertension who reach term and remain well. Methods and findings This 50-centre, open-label, randomised trial in the United Kingdom included an economic analysis. WILL randomised women with chronic or gestational hypertension at 36 to 37 weeks and a singleton fetus, and who provided documented informed consent to "Planned early term birth at 38+0-3 weeks" (intervention) or "usual care at term" (control). The coprimary outcomes were "poor maternal outcome" (composite of severe hypertension, maternal death, or maternal morbidity; superiority hypothesis) and "neonatal care unit admission for ≥4 hours" (noninferiority hypothesis). The key secondary was cesarean. Follow-up was to 6 weeks postpartum. The planned sample size was 540/group. Analysis was by intention-to-treat. A total of 403 participants (37.3% of target) were randomised to the intervention (n = 201) or control group (n = 202), from 3 June 2019 to 19 December 2022, when the funder stopped the trial for delayed recruitment. In the intervention (versus control) group, losses to follow-up were 18/201 (9%) versus 15/202 (7%). In each group, maternal age was about 30 years, about one-fifth of women were from ethnic minorities, over half had obesity, approximately half had chronic hypertension, and most were on antihypertensives with normal blood pressure. In the intervention (versus control) group, birth was a median of 0.9 weeks earlier (38.4 [38.3 to 38.6] versus 39.3 [38.7 to 39.9] weeks). There was no evidence of a difference in "poor maternal outcome" (27/201 [13%] versus 24/202 [12%], respectively; adjusted risk ratio [aRR] 1.16, 95% confidence interval [CI] 0.72 to 1.87). For "neonatal care unit admission for ≥4 hours," the intervention was considered noninferior to the control as the adjusted risk difference (aRD) 95% CI upper bound did not cross the 8% prespecified noninferiority margin (14/201 [7%] versus 14/202 [7%], respectively; aRD 0.003, 95% CI -0.05 to +0.06), although event rates were lower-than-estimated. The intervention (versus control) was associated with no difference in cesarean (58/201 [29%] versus 72/202 [36%], respectively; aRR 0.81, 95% CI 0.61 to 1.08. There were no serious adverse events. Limitations include our smaller-than-planned sample size, and lower-than-anticipated event rates, so the findings may not be generalisable to where hypertension is not treated with antihypertensive therapy. Conclusions In this study, we observed that most women with chronic or gestational hypertension required labour induction, and planned birth at 38+0-3 weeks (versus usual care) resulted in birth an average of 6 days earlier, and no differences in poor maternal outcome or neonatal morbidity. Our findings provide reassurance about planned birth at 38+0-3 weeks as a clinical option for these women. Trial registration isrctn.com ISRCTN77258279.